2022
DOI: 10.1111/den.14468
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ablation therapy for the pancreatic neoplasms

Abstract: Recently, endoscopic ultrasound (EUS)‐guided ablation therapy has been reported as a less invasive therapy for patients with pancreatic neoplasms. Some ablation techniques, including injective ablation (using ethanol or other ablative agents), radiofrequency ablation (RFA), photodynamic therapy, and laser ablation, have been described in the literature. Among these, injective ablation and RFA are more frequently used for treating pancreatic neoplasms. Few studies have evaluated the effectiveness of EUS‐guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Garg et al ( 81 ) conducted a comparative analysis of the clinical and technical success rates, as well as AEs, associated with the two techniques for pancreatic NETs, revealing no substantial differences. However, EUS-RFA demonstrates a higher complete response (CR) rate for tumors ( 82 ). Conversely, EUS-EA exhibits a higher CR rate but has a greater frequency of AEs in cases of cystic lesions ( 73 ).…”
Section: Endoscopic Ultrasound-guided Ablationmentioning
confidence: 99%
“…Garg et al ( 81 ) conducted a comparative analysis of the clinical and technical success rates, as well as AEs, associated with the two techniques for pancreatic NETs, revealing no substantial differences. However, EUS-RFA demonstrates a higher complete response (CR) rate for tumors ( 82 ). Conversely, EUS-EA exhibits a higher CR rate but has a greater frequency of AEs in cases of cystic lesions ( 73 ).…”
Section: Endoscopic Ultrasound-guided Ablationmentioning
confidence: 99%
“…Specifically, EUS-guided fine needle injection (EUS-FNI) has been regarded as a feasible and minimally invasive interventional option for local management of PC. 18 In 2016, a study demonstrated that EUS-guided intramural injection of GEM is feasible and potentially effective for treating locally advanced PC. 19 However, benefits were limited because of the rapid clearance of GEM and the advanced stage of cancer in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have demonstrated that ultrasound endoscopy-guided injection ablation, as well as ultrasound or computed tomography (CT)-guided radiofrequency ablation, are safe and feasible minimally invasive treatment methods for insulinoma. These approaches have been shown to have signi cantly lower operational di culties, complications, and medical costs compared to traditional surgery [10][11][12][13][14] . Furthermore, they are less challenging, less complex, and more cost-effective than conventional surgical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Although ethanol is a traditional ablative agent, its use can be associated with complications such as pancreatitis, peritonitis, pancreatic pseudocysts, as well as hematomas and ulcers in adjacent organs [7,14] . Extensive efforts have been made to enhance the e cacy and safety of ablative therapy for insulinomas, leading to the exploration of various drugs in recent years.…”
Section: Introductionmentioning
confidence: 99%